Serum osteocalcin levels in overweight children - Seok Bin Oh; Won Young Lee; Hyo-Kyoung Nam; Young-Jun Rhie; Kee-Hyoung Lee (Korean Society of Pediatric Endocrinology, 2019)
Purpose Bone plays a role in glucose metabolism through the release of uncarboxylated osteocalcin into the systemic circulation. The identified novel roles for osteocalcin include increasing insulin secretion and sensitivity, energy expenditure, reduction of fat mass, and mitochondrial proliferation and functional enhancement. This study aimed to determine serum osteocalcin levels in overweight children and to investigate the relationships of osteocalcin with glucose metabolism and insulin sensitivity. Methods After overnight fasting, serum osteocalcin levels were measured in overweight (n=50) children between 6.0 and 12.9 years of age and nonoverweight controls (n=60). Height, weight, fasting serum glucose, insulin, alkaline phosphatase, total cholesterol, and 25 hydroxy vitamin D3 (25(OH)VitD3) were also measured in all subjects. Results There were significant differences in serum osteocalcin levels between the overweight and control groups (64.00±20.44 vs. 89.56±28.63, P<0.001). Serum osteocalcin levels were inversely correlated with body mass index (BMI) (r=-0.283, P=0.003), weight standard deviation score (SDS) (r=-0.222, P=0.020), BMI SDS (r=-0.297, P=0.002), insulin (r=-0.313, P=0.001), and homeostasis model assessment of insulin resistance (HOMA-IR) index (r=-0.268, P=0.005). In the subsequent multiple regression analyses, BMI, HOMA-IR, and age were determined to be independent predicting factors for serum osteocalcin. Conclusions Our findings showed associations of serum osteocalcin with glucose metabolism and insulin sensitivity in overweight children, but we could not establish a causal relationship.